Regional policy from a supra-regional perspective - Ugo Fratesi (European Regional Science Association (ERSA), 2004)
A large number of economic models has been developed in the past 15 years in order to explore the causes of endogenous regional growth and the location of economic activities with the consequent differentials of development among territories. At the same time regional policies have undergone major modifications with increasing importance attributed to bottom up policies and to the efficiency of spending, also due to a situation in which funds are a scarce resource. These developments appear however to have taken place without paying enough attention to the concurrent effects entailed by policies implemented separately by different regions. In fact competing regions can implement policies which are not optimal from an aggregate point of view. At the same time national policies designed to reduce regional inequalities may also be sub-optimal from a country perspective. Unfortunately, it is too often unclear under what values of the parameters regional policies are also able to increase the aggregate economic performance of nations or over-national communities and which policies are, instead, to be simply considered as a means to increase the equality of income across space. Therefore it is on the one hand important to detect which regional policies belong to each of the two categories, then to compare them with different policies (aiming at equality of income or at efficiency) to discover which ones are better suited to achieve the needed results with lower costs. On the other hand, it is important to further investigate which policies are more fruitful if implemented in a context of regional competition and which ones should be top-down. This article addresses the issues presented above. First there is a revision of the existing contributions in order to evidence the general tendencies of the existing literature, the results that can already be considered as achieved and the deficiencies that limit the ability to produce usable policy prescriptions. Then the paper analyses the relationship between regional policies and national competitiveness in a small number of selected existing models of regional growth and localisation, in particular with an extension to the case of competing countries, each composed of more than one region.
Keywords: 330